Fire‐induced population reduction and landscape opening increases gene flow via pollen dispersal in Pinus halepensis. Issue 1 (15th October 2013) - Shohami, D.; Nathan, R.
Abstract Population reduction and disturbances may alter dispersal, mating patterns and gene flow. Rather than taking the common approach of comparing different populations or sites, here we studied gene flow via wind‐mediated effective pollen dispersal on the same plant individuals before and after a fire‐induced population drop, in a natural stand of Pinus halepensis. The fire killed 96% of the pine trees in the stand and cleared the vegetation in the area. Thirteen trees survived in two groups separated by 80 m, and seven of these trees had serotinous (closed) prefire cones that did not open despite the fire. We analysed pollen from closed pre and postfire cones using microsatellites. The two groups of surviving trees were highly genetically differentiated, and the pollen they produced also showed strong among‐group differentiation and very high kinship both before and after the fire, indicating limited and very local pollen dispersal. The pollen not produced by the survivors also showed significant prefire spatial genetic structure and high kinship, indicating mainly within‐population origin and limited gene flow from outside, but became spatially homogeneous with random kinship after the fire. We suggest that postfire gene flow via wind‐mediated pollen dispersal increased by two putative mechanisms: (i) a drastic reduction in local pollen production due to population thinning, effectively increasing pollen immigration through reduced dilution effect; (ii) an increase in wind speeds in the vegetation‐free postfire landscape. This research shows that dispersal can alleviate negative genetic effects of population size reduction and that disturbances might enhance gene flow, rather than reduce it.